Christianity, Islam, Judaism, and unwillingness to donate organs post-mortem. Issue 2 (7th February 2022) - Tarabeih, Mahdi; Abu-Rakia, Riad; Bokek-Cohen, Ya'arit; Azuri, Pazit
Abstract: Willingness to donate organs is contingent upon knowledge about and attitude toward organ donation. In order to explore differences between members of the three monotheistic religions: Christianity, Islam, and Judaism, a nation-wide survey was conducted in Israel. Members of all three religions expressed a very low willingness to donate organs postmortem. They had similar levels of knowledge regarding organ donation and similar negative attitudes toward organ donation. The public feels negative regarding the issue, therefore education campaigns should be designed and implemented in order to refute potential misconceptions and hence increase the number of people who sign donor cards.